The Effect of Introduction School Fields and Interest on Students' Readiness to Become Teachers - Fena Dwi Moeriyati; Siti Sri Wulandari (Economic Education Analysis Journal, 2023)
This study aimed to determine the effect of Introduction Field Schools (PLP) and interest in students' readiness to become teachers. Readiness to become a teacher is a readiness that exists in individuals who already have knowledge and skills in the teaching profession so that they can carry out their duties and obligations as a teacher. Initial observations show that the readiness of FEB Unesa Education Study Program students to become teachers still needs to improve. In this study, students of the Faculty of Economics and Business, Surabaya State University, class of 2019, were used as subjects of four study programs: the Economics Education Study Program, Office Administration Education, and Accounting and Commerce Education. The type of research used is descriptive quantitative. Data collection techniques using a questionnaire. The analytical method used is instrument testing using validity and reliability tests and hypothesis testing using multiple linear regression. The results showed that simultaneously the independent variables were: (1) PLP had a positive and significant effect on student readiness to become teachers; (2) Interest had a positive and significant effect on student readiness to become teachers; (3) PLP and interest had a positive and significant effect on student readiness to become teachers.